Democracy at dawn : notes from Poland and points East - Quinn, Frederick (Eastern European studies (College Station, Tex.) ;, 1998)
From 1993 to 1995, the author, "traveled the former Soviet empire as head of the rule of law programs of the Warsaw Office of Democratic Institutions and Human Rights (ODIHR), part of the Organization fro Sceurity and Cooperation in Europe (OSCE). His primary task was to help the new nations of the region write new constitutions and modernize their judicial systems."